Quality of the Evidence Supporting the Role of Acupuncture for Stable Angina Pectoris: An Umbrella Review of Systematic Reviews - Min Shen; Min Shen; Jinke Huang; Tao Qiu; Tao Qiu (Frontiers in Cardiovascular Medicine, 2021)
Background: To systematically appraise and synthesize evidence, we conducted an overview of systematic reviews/meta-analyses (SRs/MAs) on acupuncture for stable angina pectoris (SAP).Methods: Eight databases were searched for SRs/MAs of acupuncture on SAP. The methodological quality, reporting quality, and evidence quality were evaluated by Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2), the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist, and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system, respectively.Results: A total of seven published SRs/MAs met the inclusion criteria. According to the evaluation results of AMSTAR-2, two studies were considered as of moderate quality; the remaining five were considered as of very low quality. According to the evaluation results of the PRISMA checklist, only one study reported the checklist in its entirety, while others had reporting deficiencies. According to GRADE, a total of 18 outcome indicators extracted from the included studies were evaluated. The evidence quality was very low in three, low in three, moderate in eight, and high in four.Conclusion: Acupuncture may be beneficial for SAP from the currently published evidence. However, this conclusion must be interpreted cautiously due to the generally low methodological quality, reporting quality, and evidence quality of the included studies. More rigorous, more standardized and comprehensive SRs/MAs are needed to provide strong evidence for convincing conclusions.